دور التعليم القائم على النواتج : مهارة الاتصال باللغة العربية أنموذجا - روينسكي، رزقا (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
The aim of this research is to study the role of outcomes-based education in enhancing communication skills in Arabic language among students of the International Islamic University of Malaysia from the Arabic and Islamic Studies Departments. The research seeks to identify the useful educational activities among students and their impacts and the obstacles to the application of outcomes-based education in enhancing their communication skills. The researcher relied on the descriptive approach by using survey. The data were collected through the questionnaire from the previous studies and distributed to 234 students. The study found that activities such as practicing words activity, games and watching movies help students in improving communication skills. The educational activities help students to develop communication skills according to the necessary elements, but they do not really encourage them to give comments and answer the questions. The results of the study found that, students on average generally do not face many obstacles in enhancing communication skills in the light of outcomes-based education. However, the result showed that the large number of students in one class, students' unwillingness to communicate and participate in activities, and not revising the previous lesson might hinder the application of outcome-based education and their ability to communicate in Arabic Language.